Accurate estimation of the inhibition zone of antibiotics based on laser speckle imaging and multiple random speckle illumination - Kim, Donghyeok; Lee, Jongseo; Yoon, Jonghee (Computers in Biology and Medicine, 2024)
The antimicrobial susceptibility test (AST) plays a crucial role in selecting appropriate antibiotics for the treatment of bacterial infections in patients. The diffusion disk method is widely adopted AST method due to its simplicity, cost-effectiveness, and flexibility. It assesses antibiotic efficacy by measuring the size of the inhibition zone where bacterial growth is suppressed. Quantification of the zone diameter is typically achieved using tools such as rulers, calipers, or automated zone readers, as the inhibition zone is visually discernible. However, challenges arise due to inaccuracies stemming from human errors or image processing of intensity-based images. Here, we proposed a bacterial activity-based AST using laser speckle imaging (LSI) with multiple speckle illumination. LSI measures a speckle pattern produced by interferences of scattered light from the sample; therefore, LSI enables the detection of variation or movement within the sample such as bacterial activity. We found that LSI with multiple speckle illuminations provides consistent and uniform analysis of measured time-varying speckle images. Furthermore, our proposed method effectively identified the boundary of the inhibition zone using the k-means clustering algorithm, exploiting a result of speckle pattern analysis as features. Collectively, the proposed method offers a versatile analytical tool in the diffusion disk method.
Keywords: Accurate estimation; Antimicrobial susceptibility; Bacterial infections; Bacterials activities; Diffusion disk method; Inhibition zones; Laser-speckle imaging; Random speckle; Susceptibility tests; Zone of inhibitions; Algorithms; Anti-Bacterial Agents; Humans; Image Processing, Computer-Assisted; Lasers; Microbial Sensitivity Tests; Antibiotics; Diffusion disk method; Laser speckle imaging; Random speckle; Zone of inhibition